Convective flow and heat transfer from wavy surfaces : viscous fluids, porous media, and nanofluids /: viscous fluids, porous media, and nanofluids. (2016) - Shenoy, Aroon V, 1951-; Sheremet, Mikhail; Pop, Ioan, 1937-
No abstract available